Structural Studies on Nuphar Alkaloids - Martin, Ian Trevor (My University, 1974)
The mass spectra of several quinolizidine alkaloids of known structure, isolated from species of Nuphar luteum, have been studied. High resolution mass measurements have been used to characterise fragmentation patterns capable of differentiating between substituents in rings A and B of the quinolizidine system.
The stereoisomeric relationship between the thiospiran Nuphar alkaloids, thiobinupharidine and neothiobinupharidine, has been examined. A three-dimensional structure has been proposed for thiobinupharidine on the basis on its spectroscopic properties. An X-ray study has confirmed this structure and also established the absolute configuration of thiobinupharidine.
The structure of three new alkaloids, nupharolutine, thionupharoline, and neothiobinupharidine sulphoxide, have been established on the basis of mass spectral and p.m.r. data.
The steric course of sodium borodeuteride reduction of hemiaminals of thiobinupharidine in absolute ethanol solution has been investigated. Significant differences have been observed for both the degree of deuterium incorporation and for the stereoselectivity of deuterium incorporation when compared to those results reported for analogous reductions in methanol solution. The transient intermediacy of an alkoxyborodeuteride ion has been proposed to explain these results.
Keywords: Chemistry; Chemistry